2013
DOI: 10.4103/0973-1482.126464
|View full text |Cite
|
Sign up to set email alerts
|

The demonstration of extension of high-grade glioma beyond magnetic resonance imaging defined edema by the use of 11 C-methionine positron emission tomography

Abstract: The use of magnetic resonance imaging (MRI) is the current standard for the delineation of target volumes for high-grade gliomas (HGG). While the peritumoral edema as per T2-weighted (T2W) imaging is utilized as basis to delineate the initial borders of the clinical target volume (CTV), those areas enhancing on T1-weighted (T1W) images with gadolinium contrast (T1-Gd) are considered for treatment with further boost. However, recent data has emerged concerning the use of positron emission tomography (PET) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In addition, the level of normalized pyruvate in the contralateral brain tissue of the enhancing tumor was significantly smaller than those in the ipsilateral lesion and the contralateral brain tissue of the non-enhancing tumor. Unlike clinical glioblastoma, which carries highly infiltrative tumor characteristics, with tumor cells extending beyond the boundary of contrast enhancement and T2 hyperintensity [21][22][23], the preclinical model of glioblastoma using the U87-MG cell line has been shown to maintain relatively welldemarcated tumor margins in anatomical MRI and pathological slides [24]. Our result from the H&E stain of the enhancing tumor was consistent with this finding, displaying a clearly delineated tumor boundary without noticeable tumor infiltration into the nearby brain tissue (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the level of normalized pyruvate in the contralateral brain tissue of the enhancing tumor was significantly smaller than those in the ipsilateral lesion and the contralateral brain tissue of the non-enhancing tumor. Unlike clinical glioblastoma, which carries highly infiltrative tumor characteristics, with tumor cells extending beyond the boundary of contrast enhancement and T2 hyperintensity [21][22][23], the preclinical model of glioblastoma using the U87-MG cell line has been shown to maintain relatively welldemarcated tumor margins in anatomical MRI and pathological slides [24]. Our result from the H&E stain of the enhancing tumor was consistent with this finding, displaying a clearly delineated tumor boundary without noticeable tumor infiltration into the nearby brain tissue (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing GBM and WHO grade III gliomas, BraTumIA performed significantly better in accuracy for GBM than for grade III tumors. One possible reason for this result may be associated with the gadolinium-enhancing characteristics of the tumor, since contrast enhancement of the tumor is known to be associated with glioma grade (19,31). Porz et al (20) demonstrated that BraTumIA could detect the contrast-enhancing tumor region with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Sites of blood-brain barrier disruption on contrast-enhanced T1-weighted (T1w) images are used as surrogate markers for active tumor regions; however, tumor cells can exist beyond the identified regions (16). Furthermore, it has been demonstrated that T2-weighted (T2w) hyperintense regions can contain tumors (17,18), whereas Susheela et al (19) reported a case of a high grade glioma which was present beyond the MRI defined edema region, and was demonstrated using 11 C-methionine positron emission tomography (MET-PET) (19). A single MRI sequence may therefore be insufficient to identify tumor regions.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) with metabolic tracers has played an important role in neurooncology [8,9]. Radiolabelled amino acids, such as 11 C-methionine (MET) PET, reflect the extent of tumour boundaries in GBM more reliably than CT or MRI, because Gd-enhanced areas in MRI represent disruptions of the brain-blood barrier, while MET uptake correlates with tumour cell density or proliferative capability, thus more closely reflecting the properties of glioblastoma multiforme [10][11][12][13]. Complete resection of MET uptake areas has been shown to increase survival of high-grade glioma patients in previous studies [14,15].…”
Section: Introductionmentioning
confidence: 99%